Recent Progress on Adsorption Materials for Phosphate Removal - Ahmed, Saeed; Ashiq, Muhammad N.; Li, Dianqing; Tang, Pinggui; Leroux, Fabrice; Feng, Yongjun (Recent Patents on Nanotechnology, 2019)
Background: High concentration of phosphate has been threatening human health and the ecosystem. Adsorption is one of high-efficiency and low-cost techniques to reduce the concentration of phosphate. This mini review aims to summarize the recent development of adsorption materials for phosphate removal. Method: We conducted a detailed search of “adsorption of phosphate” in the published papers and the public patents on the adsorbents for phosphate based on Web of Science database in the period from January 1 2012 to December 31 2017. The corresponding literature was carefully evaluated and analyzed. Results: One hundred and forty one papers and twenty two recent patents were included in this review. An increased trend in scientific contributions was observed in the development of adsorption materials for phosphate removal. Three kinds of promising adsorbents: layered double hydroxides, natural materials, and metal oxides were paid special attention including removal mechanism, performance as well as the relationship between adsorption performance and structure. Both the chemical composition and the morphology play a key role in the removal capacity and rate. Conclusion: The findings of this review confirm the importance of phosphate removal, show the development trend of high-performance and low-cost adsorption materials for phosphate removal, and provide a helpful guide to design and fabricate high-efficiency adsorbents.
Keywords: Adsorption process